2018
DOI: 10.1016/j.gie.2018.08.018
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of histologic disease activity assessment in ulcerative colitis

Abstract: Although rarely used to measure inflammation and guide therapy, histologic disease activity is predictive of important clinical outcomes in UC. Randomized controlled trials are needed to determine whether histology should function as a treatment target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
91
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(96 citation statements)
references
References 53 publications
(84 reference statements)
1
91
0
4
Order By: Relevance
“…12 Nevertheless, quantification of inflammation on endoscopic biopsies seems to be a clinically relevant goal in CD trials, given recent developments in validating tools for histologic assessment in ulcerative colitis trials. 13 Vedolizumab is an anti-a4b7-integrin humanized immunoglobulin G1 monoclonal antibody that selectively blocks T-lymphocyte trafficking into the gastrointestinal mucosa. 14 The pivotal GEMINI 2 and 3 trials of vedolizumab in moderately to severely active CD demonstrated the benefit of vedolizumab on clinical outcomes; however, these studies did not include endoscopic, radiologic, or histologic assessments.…”
mentioning
confidence: 99%
“…12 Nevertheless, quantification of inflammation on endoscopic biopsies seems to be a clinically relevant goal in CD trials, given recent developments in validating tools for histologic assessment in ulcerative colitis trials. 13 Vedolizumab is an anti-a4b7-integrin humanized immunoglobulin G1 monoclonal antibody that selectively blocks T-lymphocyte trafficking into the gastrointestinal mucosa. 14 The pivotal GEMINI 2 and 3 trials of vedolizumab in moderately to severely active CD demonstrated the benefit of vedolizumab on clinical outcomes; however, these studies did not include endoscopic, radiologic, or histologic assessments.…”
mentioning
confidence: 99%
“…Recommendations for assessing histological activity in UC, as proposed by various experts and the ECCO guidelines 6,7,12,13 include examination of 2 properly fixed biopsies sampled from each segment of colon, including rectum and terminal ileum, especially from the most affected areas (particularly ulcers). This sampling pattern would increase the likeliness to adequately assess the presence and severity of lesions as UC may have discontinuous appearance as consequence of natural evolution or as effect of treatment 1 .…”
Section: Discussionmentioning
confidence: 99%
“…The goals of medication therapy are  inducing and maintaining remission  improving the person's quality of life. Many people with ulcerative colitis require medication therapy indefinitely, unless they have their colon and rectum surgically removed [14,15].Health care providers will prescribe the medications that best treat a person's symptoms:aminosalicylates,corticosteroids,immunomodulator s,biologics, also called anti-TNF therapies,other medications [16]. Depending on the location of the symptoms in the colon, health care providers may recommend a person take medications by:enema, which involves flushing liquid medication into the rectum using a special wash bottle.…”
Section: Discussionmentioning
confidence: 99%